Effects of decreased specific glutathione reductase activity in a chromate-tolerant mutant of Schizosaccharomyces pombe - Koósz, Zs; Gazdag, Z; Miklós, I; Benko, Z; Belágyi, J; Antal, J; Meleg, B; Pesti, M (Folia microbiologica, 2008)
A chromate-tolerant mutant chr1-663T bearing a stable one-gene mutation and its parental strain 6chr(+) were used to investigate the background of Cr(VI) tolerance in the fission yeast Schizosaccharomyces pombe. The mutant chr1-663T displayed a significantly decreased specific glutathione reductase (GR) activity coded by the pgr1 (+) gene compared with its parental strain. Transformants of the mutant chr1-663T with a nonintegrative pUR18N vector expressing the pgr1 (+) gene exhibited the same Cr(VI) sensitivity and specific GR activity as their parental strain, demonstrating the importance of the GR-NADPH system in Cr(VI) tolerance. Transformants, nevertheless, exhibited an increased intracellular peroxide concentration, a decreased Cr(VI)-reducing and HO*-producing ability, which suggested an unbalanced oxidoreduction state of cells and partial complementation of the GR function. No mutation was found in the sequences of the pgr1 (+) and the pap1 (+) (transcriptional regulatory gene of GR) genes of the Cr(VI)-tolerant mutant by sequence analysis.
Keywords: glutathionreduktasa; down regulace; Schizosaccharomyces pombe - proteiny; oxidace-redukce; Schizosaccharomyces; Glutathione Reductase; Schizosaccharomyces pombe Proteins; fungální léková rezistence; Chromates; mutace; Down-Regulation; Drug Resistance, Fungal; Mutation; Oxidation-Reduction; chromany; Pancreatitis-Associated Proteins; proteiny asociované s pankreatitidou